Circulating Tumor DNA Detection for Recurrence Monitoring of Stage I Non‐Small Cell Lung Cancer Treated With Microwave Ablation - Lin Cheng; Sheng Xu; Yu‐feng Wang; Sheng‐wei Li; Bin Li; Xiao‐Guang Li (Thoracic Cancer, 2025)
ABSTRACT Purpose As microwave ablation continues to be used in patients with inoperable stage I non‐small cell lung cancer (NSCLC), it is particularly important to monitor efficacy. Whether plasma ctDNA detection can predict its efficacy should be illustrated. Methods We recruited 43 patients with inoperative stage I NSCLC, all of whom underwent biopsy‐synchronous microwave ablation (MWA). Peripheral blood samples were collected at baseline (n = 43), within 1 h post‐MWA (n = 28), and at the landmark time point (n = 26) for MRD detection. Clinical outcomes were analyzed using Kaplan–Meier survival analysis. Results Patients with undetectable ctDNA at baseline (p = 0.042) and within 1 h after MWA (p = 0.023) had better clinical outcomes. In particular, patients with undetectable ctDNA at the 1‐h post‐MWA time point did not experience recurrence. Detection of ctDNA at the landmark time point is considered an independent risk factor for prognosis and is strongly correlated with clinical outcomes (p = 0.001), the median time to recurrence indicated by ctDNA was 4.9 months earlier compared to imaging. The clinical outcomes of patients with ctDNA clearance were similar to those with no ctDNA (p = 0.570). Risk stratification indicated that patients with persistent ctDNA had worse clinical outcomes compared to those who never had detectable ctDNA (p = 0.004). Conclusion Our findings suggest that ctDNA monitoring can assist in predicting clinical outcomes in stage I NSCLC treated with microwave ablation. Patients with undetectable ctDNA within 1 h after MWA are determined to be clinically cured. Risk stratification based on ctDNA test results helps to differentiate high‐risk patients.